Single nucleotide polymorphisms in the growth hormone gene of Oreochromis niloticus and their association with growth performance - Khalil Jaser, Suhaila Karim; Dessimoni Dias, Marco Aurelio; Lago, Aline de Assis; Reis Neto, Rafael Vilhena [UNESP]; Silva Hilsdorf, Alexandre Wagner (Wiley-Blackwell, 2017)
Polymorphisms in the growth hormone (GH) gene that is associated with the growth rate of farmed fish have been the target of many breeding programmes. The present study aimed to identify single nucleotide polymorphisms (SNPs) in GH gene regions to evaluate the association of SNP variations with the growth rate of two Nile tilapia: Oreochromis niloticus (Linnaeus, 1758) strains. The targeted regions were amplified, sequenced, aligned and screened for the presence of SNPs; thereafter, performance tests were used to check for the association between SNPs and weight. Allele and genotype frequencies were estimated for each SNP and genotype. Genotype blocks or sets of SNP genotypes and frequencies were also estimated. Association between SNPs and growth rate was statistically evaluated using a univariate linear mixed model that included both fixed and random effects. A total of 10 SNPs were identified, nine in the proximal promoter and one located in the 5 UTR, forming 10 genotype blocks. In all weight recordings, five genotype blocks were significantly associated with the highest weights. Single nucleotide polymorphisms 6-10 were also found to be significantly associated with growth (p-value<.05). Genotypes with higher additive genetic values for weight were identified in the Chitralada strain, suggesting a possible impact of these additive effects of the GH SNP genotype on the growth rate of Nile tilapia. These findings may be used as part of marker-assisted selection in tilapia breeding programmes.
Keywords: aquaculture; growth hormone; Nile tilapia; polymorphism; single nucleotide polymorphism